Patterns of long acting injectable antipsychotic use and associated clinical factors in schizophrenia among 15 Asian countries and region - Tang, Chao Tian; Chua, Ee Cheong; Chew, Qian Hui; He, Yan‐Ling; Si, Tian‐Mei; Chiu, Helen F.‐K.; Xiang, Yu‐Tao; Kato, Takahiro A.; Kanba, Shigenobu; Shinfuku, Naotaka; Lee, Min‐Soo; Park, Seon‐Cheol; et al. (Asia-Pacific Psychiatry, 2020)
Introduction Patterns of clinical use of long‐acting injectable (LAI) antipsychotic drugs in many countries, especially in Asia, for treatment of patients diagnosed with chronic psychotic disorders including schizophrenia are not well established. Methods Within an extensive research consortium, we evaluated prescription rates for first‐ (FGA) and second‐generation antipsychotic (SGA) LAI drugs and their clinical correlates among 3557 subjects diagnosed with schizophrenia across 15 Asian countries and region. Results Overall, an average of 17.9% (638/3557; range: 0.0%‐44.9%) of treated subjects were prescribed LAI antipsychotics. Those given LAI vs orally administered agents were significantly older, had multiple hospitalizations, received multiple antipsychotics more often, at 32.4% higher doses, were more likely to manifest disorganized behavior or aggression, had somewhat superior psychosocial functioning and less negative symptoms, but were more likely to be hospitalized, with higher BMI, and more tremor. Being prescribed an FGA vs SGA LAI agent was associated with male sex, aggression, disorganization, hospitalization, multiple antipsychotics, higher doses, with similar risks of adverse neurological or metabolic effects. Rates of use of LAI antipsychotic drugs to treat patients diagnosed with schizophrenia varied by more than 40‐fold among Asian countries and given to an average of 17.9% of treated schizophrenia patients. We identified the differences in the clinical profiles and treatment characteristics of patients who were receiving FGA‐LAI and SGA‐LAI medications. Discussion These findings behoove clinicians to be mindful when evaluating patients' need to be on LAI antipsychotics amidst multifaceted considerations, especially downstream adverse events such as metabolic and extrapyramidal side effects.